Capacity Building Model of Urban Farmer Groups through Participatory Mapping and Visual Dissemination - Tisnawati, Endah; Yuamita, Ferida; Saptoto, Anang; Sagio, Sagio; Kyswantoro, Yunita Firdha; Ratriningsih, Desrina (Universitas Ahmad Dahlan, 2025)
Background: Urban agriculture is a strategy to overcome the limitations of agricultural land in urban areas, while contributing to food security and community involvement. This community service program aims to strengthen the institutional capacity of urban farmer groups in Kemantren Gondokusuman, Yogyakarta. The main objective of this activity is to improve the institutional capacity of farmer groups and strengthen the economic resilience of the group. Contribution: This program promotes more inclusive decision-making for farmer groups and improves access to institutional resources, contributing to the sustainability of urban agriculture. Method: The approach used includes participatory mapping to identify the potential of farmer groups, exhibitions as a medium for interactive dissemination, and focus group discussions (FGD) to formulate institutional strategies and economic strengthening. Data was collected through field observations, structured interviews, and community workshops. Results: The results show that participatory mapping increases collective awareness among farmer group members regarding available resources, expands interactions among stakeholders (farmer group members, the community, and academics), and facilitates knowledge exchange. Structured FGDs support the formulation of institutional strategies, leading to increased group cohesion, managerial transparency, and broader access to external support. This combination of methods demonstrates that integrated strategies can enhance the institutional effectiveness of urban farming groups. Conclusion: The integration of participatory methods and public interaction plays a crucial role in strengthening the capacity of urban farming groups. This program provides a replicable implementation model for other communities and demonstrates that the sustainability of urban farming depends on institutional strengthening and community engagement.